Restored Macrophage Function Ameliorates Disease Pathophysiology in a Mouse Model for IL10 Receptor-deficient Very Early Onset Inflammatory Bowel Disease. (17th February 2021) - Ackermann, Mania; Mucci, Adele; McCabe, Amanda; Frei, Sandy; Wright, Kayla; Snapper, Scott B; Lachmann, Nico; Williams, David A; Brendel, Christian
Abstract: Background and Aims: Mutations in IL10 or the IL10 receptor lead to very early onset [VEO] inflammatory bowel disease [IBD], a life-threatening disease which is often unresponsive to conventional medication. Recent studies have demonstrated that defective IL-10 receptor signalling in innate immune cells is a key driver of severe intestinal inflammation in VEO-IBD. Specifically, IL10 unresponsiveness of macrophages, which govern the tight balance between pro- and anti-inflammatory responses in the intestinal system, plays a central role in the events leading to excessive inflammatory responses and the development of IBD. Methods and Results: We here evaluated haematopoietic stem cell gene therapy in a VEO-IBD mouse model and demonstrated that the therapeutic response closely correlates with gene correction of the IL10 signalling pathway in intestinal macrophages. This finding prompted us to evaluate the therapeutic efficacy of macrophage transplantation in the Il10rb -/- VEO-IBD mouse model. A 6-week regimen employing a combination of depletion of endogenous hyperinflammatory macrophages followed by intraperitoneal administration of wild-type [WT] macrophages significantly reduced colitis symptoms. Conclusions: In summary, we show that the correction of the IL10 receptor defect in macrophages, either by genetic therapy or transfer of WT macrophages to the peritoneum, can ameliorate disease-related symptoms and potentially represent novel treatment approaches for VEO-IBD patients.